Where have all the behaviorists gone? - Branch, Marc N. (1980)
Many of the world's current problems are the result of behavior, and traditional appeals to mental determinants are again proving inadequate. The time for a behavioristic alternative appears ripe, yet many behaviorists seem to be becoming less behavioristic and more mentalistic. When confronted with the complexity of human behavior many are resorting to the intellectual comfort and safety of mentalism. A recent example of this tendency (Schwartz et al, 1978) is presented and discussed. Additionally, speculations regarding the origins of the resurgence of mentalism are presented, and it is proposed that arranging histories which provide for more rigorous and lasting control of verbal behavior about behavior may serve to improve the situation.